A EDUCAÇÃO COMO VETOR DE DESENVOLVIMENTO SOCIAL EM PEQUENOS MUNICÍPIOS. - PERUZZO, JOBERT; NARDI, ELTON LUIZ (Impulso)
This paper discusses the role in small Brazilian municipalities in educational matters from their administrative political emancipation. It aims to analyze the elements that inform the performance of small municipalities in the field of public education, considering the social development expectations that are nurtured by the population. The empirical research was made in two small municipalities of Santa Catarina and the methodological procedures were based in the qualitative research assumptions and operated by consulting the official databases and interviews with people that represent the population. The results conclude that the performance of the municipalities in the educational policy field, although under the influence of different factors, correspond to social development expectations of the population. Also, a better response from public power to these expectations is through the involvement of the population in matters of public interest.